PENGARUH TINGKAT KESEHATAN BANK TERHADAP PERTUMBUHAN LABA PADA BPR DI INDONESIA - Anisah Lubis (Ekonomi dan Keuangan, 2013)
This study aimed to test whether a bank's health is represented by the Adequency Capital Ratio (CAR), Non Performing Loan (NPL), ROA and Loan to Deposit Ratio (LDR) effect on earnings growth BPR in the period 2008-2012.The data used in this study were obtained from the publication of the financial statements BPR, which have been audited and published by Bank Indonesia. The F test results indicate that the variable Adequency Capital Ratio (CAR), Non Performing Loan (NPL), BOPO and Loan to Deposit Ratio (LDR) simultaneously significant effect on the variable profit growth, while partially by using the t test showed that the variables Adequency Capital Ratio (CAR) has a significant negative correlation with profit growth. Variable Non Performing Loan (NPL) in this study had a positive relationship with profit growth while variable BOPO and the Loan to Deposit Ratio (LDR) has a negative relationship with profit growth at BPR. These results show the value of adjusted R2 of 56.9%. The results of this study are expected to be taken into consideration for management in predicting the earnings growth.Keywords: Adequency Capital Ratio (CAR), Non Performing Loan (NPL), BOPO, Loan to Deposit Ratio (LDR), growth in profit.